1985
DOI: 10.1111/1523-1747.ep12277061
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Assessment of Lymph Node Weight and T-Lymphocyte Proliferation in Contact Sensitivity in Acrylates

Abstract: An assessment of T-lymphocyte proliferation and lymph node weight is proposed as a predictive test for contact sensitizers of industrial origin. Data are presented showing increased T-lymphocyte proliferation following epicutaneous application of a variety of industrially important acrylate-like chemicals which appear to correlate well with their ability to sensitize in the guinea pig. These data were compared with those obtained after application of 2,4-dinitro-1-fluorobenzene (DNFB) a strong sensitizer, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…These data are therefore in conflict with those of Som mer et al [16], who found that topical application of DNTB to guinea-pigs failed to cause an increase in the weight of the draining auricular lymph node and only a modest increase in LNC proliferation (meas ured by [l25I]iododeoxyuridine incorporation). In contrast, it was observed that in guinea-pigs, DNTB caused a marked increase in nucleic acid synthesis in the contralateral auricular node both 4 and 6 days af ter application, which was apparently due to cell pro liferation in germinal centres, the corticomedullary junction and medullary cords [16], Similar data demonstrating a significant increase in the frequency of large pyroninophilic cells in contralateral auricular lymph nodes following application of DNTB to the guinea-pig ear have recently been reported [20], In ad dition to eliciting a primary T lymphocyte response, we present evidence that in mice, rats and man, DNTB induced contact sensitization. These observa tions contrast with 3 independent studies in which DNTB was found to induce sensitization only when administered with Freund's complete adjuvant [16,17,21].…”
Section: Discussionmentioning
confidence: 68%
“…These data are therefore in conflict with those of Som mer et al [16], who found that topical application of DNTB to guinea-pigs failed to cause an increase in the weight of the draining auricular lymph node and only a modest increase in LNC proliferation (meas ured by [l25I]iododeoxyuridine incorporation). In contrast, it was observed that in guinea-pigs, DNTB caused a marked increase in nucleic acid synthesis in the contralateral auricular node both 4 and 6 days af ter application, which was apparently due to cell pro liferation in germinal centres, the corticomedullary junction and medullary cords [16], Similar data demonstrating a significant increase in the frequency of large pyroninophilic cells in contralateral auricular lymph nodes following application of DNTB to the guinea-pig ear have recently been reported [20], In ad dition to eliciting a primary T lymphocyte response, we present evidence that in mice, rats and man, DNTB induced contact sensitization. These observa tions contrast with 3 independent studies in which DNTB was found to induce sensitization only when administered with Freund's complete adjuvant [16,17,21].…”
Section: Discussionmentioning
confidence: 68%
“…The failure to raise an antibody response to TMPTA is surprising since all three compounds are able to induce contact sensi tivity reactions in guinea pigs [3,7], However, specific anti-TMPTA antibodies were produced following im munization with a TMPTA/BGG conjugate. Sera from animals immunized with conjugated TMPTA were used in experiments designed to determine an tibody specificities, using an assay system which de tected antiacrylate, but not anti-BGG, antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…1) have been in vestigated in terms of their immunogenicity as as sessed by the in vivo induction of antibody. The abil ity of the acrylates to induce antibodies and the spe cificities of these antibodies were compared with data published previously on the in vivo sensitization ca pacity and cross-reactivity between the acrylates [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In an early version of LLNA, Bull et al (Bull et al, 1985) measured lymphocyte proliferation in the draining lymph nodes of guinea pigs after topical application of MMA dissolved in acetone-olive oil. Proliferation was scored by a microscopic cell-counting method.…”
Section: In Vivo Animal Studiesmentioning
confidence: 99%